1999
DOI: 10.1177/014107689909200903
|View full text |Cite
|
Sign up to set email alerts
|

How Do General Practitioners Respond to Reports of Abnormal Chest X-rays?

Abstract: General practitioners (GPs) in the UK have long had direct access to hospital radiological services, which in theory shortens investigation time and improves the quality of service. Chest X-rays (CXRs) account for a substantial proportion of requests, and we investigated what happened when an abnormality was detected. In one year, 204 GPs in the Nottingham area requested CXRs in 605 patients. 362 were reported normal, 165 abnormal but hospital follow-up not indicated and 71 abnormal with radiological follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
“…Reported median times from the primary care visit to referral for specialist evaluation were 13 days (range 0–21 days),48 16 days,6 33 days (IQR 12–68 days)49 and 33 days (range 0–477 days) 39. Two studies demonstrated that patients often made multiple visits to their primary care physician before additional investigation were initiated 50 51.…”
Section: Resultsmentioning
confidence: 99%